Establishment, characterization, and validation of dorsal root ganglia explant cultures for drug development - Allgaier, Juulia (My University, 2023)
Pain is an unpleasant sensation that protects body against potential harm. In turn, chronic pain, is a maladaptive and pathological disease and no longer beneficial. Dorsal root ganglia (DRG) and sensory neurons inside it convey nociceptive information. DRG ex vivo explants preserve tissue-like microenvironment making them appropriate models to study neuronal functions. Aim of the project is to establish and validate rat DRG explant model, characterize the cellular composition and express foreign gene in it. Neuronal sprouting was monitored using an automated live cell imaging system (Incucyte) and quantified utilizing a combination of Incucyte’s NeuroTrack software and Qupath. Developed quantification protocol was used to study neurite growth in different experimental conditions. Immunostaining was employed to characterize cell population. Explants were transduced using recombinant adeno-associated virus (AAV). In this project, I successfully established protocols for dissection, culturing, monitoring and quantifying rat DRG explants. Results indicate that neurite growth is proportional to Matrigel concentration; being highest at 50% dilution and smallest at 10%. DRG explants show age-dependent growing, explants from young rats (37-weeks old) have higher probability to grow (8596%) than explants from older rats (9-weeks old, 48%). Immunostaining confirmed a close association between neuronal and glial cells at newly formed neurites. Sprouting results, according to developed quantification protocol, showed dependence on NGF only during the first six days in culture, while pharmacological blocking of NGF inhibited sprouting independently of NGF presence. Finally, results show that recombinant AAV vectors successfully transduced DRG neurons, suggesting their use as a tool to transfer e.g., pain related therapeutic genes.
Keywords: chronic pain, dorsal root ganglia, explant, explant culture, nerve growth factor, tropomyosin receptor kinase A